Development of Diagnostic Tests to Identify Students' Problem-Solving Difficulties in Static Fluid Material - Sri Wahyu Ningsih; Haratua Tiur Maria Silitonga; Muhammad Musa Syarif Hidayatullah (Jurnal Penelitian Pembelajaran Fisika, 2025)
The availability of diagnostic instruments specifically designed to identify students' difficulties in solving problems related to static fluids is still limited, even though this material often leads to misconceptions and conceptual difficulties. This article aims to present the results of the development of a diagnostic test instrument to identify students' problem-solving difficulties in the static fluid material. This study employs the R&D (Research and Development) method using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The validation of the test instrument was assessed by two physics education lecturers and two physics teachers, covering content and language validation. The instrument validation results were analyzed using the Aiken index formula, obtaining a value of 0.83 with a high rating for content validation and a value of 0.93 with a high rating for language validation. The respondents in this study consisted of 95 students from grade XII. The test instrument provided consisted of essay questions, with each question containing two parts related to conceptual understanding and problem-solving ability. The analysis was conducted using Winsteps software. Based on the student response survey results regarding the diagnostic test, the average response percentage was 71%, which falls within the good criteria. The results of this study can be used as a reference for the development of instruments in physics, particularly static fluids, and help teachers better understand and address students' learning difficulties.